Enantiopure β3-Trifluoromethyl-β3-homoalanine Derivatives: Coupling with Boc-Protected Amino Acids and Conformational Studies of Peptides in Solid State - Saraiva Rosa, Nathalie; Grellepois, Fabienne (Synthesis, 2022)
The use of enantiopure β3-trifluoromethyl-β3-alkyl β-amino acids for the design of peptides would contribute to drastically enhance peptide stability in vivo. Moreover, the steric hindrance generated by the substituents on the tetrasubstituted carbon adjacent to the nitrogen function coupled to the electron-withdrawing effect of the trifluoromethyl group is more likely to influence the 3D conformation of the peptide. Herein, we describe a short, scalable and robust method to synthesize N- and/or C-protected enantiopure (R)- and (S)-β3-trifluoromethyl-β3-methyl β-amino acid derivatives and liquid-phase coupling methods suitable for incorporation of Boc-protected amino acids into short α/β- and β-peptides. Conformational studies of some of these original peptides via X-ray diffraction analysis highlighted intraresidue C6 hydrogen bonds within trifluoromethylated amino acids.
Keywords: fluorine; amino acids; peptides; coupling; conformational analysis